Objeto direto anafórico no português angolano: descrição e análise sociolinguística - Santana, Jan Carlos Dias de (2024)
This research is based on the assumptions of Variationist Sociolinguistics and had as its main objective to describe the configuration of the anaphoric direct object in the Angolan Portuguese. Speech samples are analyzed, totaling 903 occurrences extracted from 36 interviews divided by the speaker's gender, education and age group. In addition, considering the multilingual context and the large migratory flow in Angolan territory, the interviews are still stratified with regard to the origin of the speaker (whether he was born in the capital of Luanda or if he comes from other provinces of the country) and the status of the L1/L2 Portuguese. The data are quantified using the statistical program GoldVarb X. Therefore, the results show that the third-person accusative clitic, considered the standard variant in the Portuguese, presented a frequency of 3%. There was a high frequency of the null object (51.7%) and the anaphoric SN (41.5%), with a frequency of only 1.2% for the full pronoun. Another variant in the Angolan vernacular Portuguese is also attested: the anaphoric accusative (2.5%), a variant not found in previous studies of the Brazilian Portuguese and the European Portuguese. Finally, it is identified which linguistic and social factors condition the use of the null object in relation to the other anaphoric direct object strategies.